Case Report: A Primary Right Ventricular Vascular Malformation Presenting as a Mass - Liu, Hongduan; Li, Xin; Zhang, Cuiwei; Fan, Chengming; Liu, Liming; Wan, Juyi (Frontiers in Cardiovascular Medicine, 2021)
Primary right ventricular vascular malformation is a rare primary benign anomaly in heart in nature. Due to the extremely low incidence and the progress on the classification of vascular malformation, a few cases were reported in the literatures. In the current case study, a 55-year-old women presented with a cardiac mass that was identified in right ventricle during a routine medical checkup. Magnetic resonance imaging demonstrated a well-circumscribed mass attached to the interventricular septum. Median sternotomy for the surgical resection of the mass and a cardiopulmonary bypass were performed. The intraoperative transesophageal echocardiogram showed that the mass had been successfully removed. The patient recovered well and was discharged from hospital 9 days after the surgery. The pathological diagnosis was primary cardiac arteriovenous malformation. No mass recurrence was shown by echocardiography during the 13 months’ follow-up.